2018
DOI: 10.2478/cerce-2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Effects of Algerian Sodium Bentonite on Growth Performance and Biochemical Parameters in Broiler Chickens

Abstract: The present experiment was conducted to investigate the effect of supplementing poultry feed with graded levels of Algerian sodium bentonite (Na-B) on growth performance and the development of villus height in jejunum and some biochemical parameters during 50 days in broiler chickens. A number of 420 one-day old broiler chicks (Arbor Acres) were obtained from a commercial hatchery. The birds were randomly allocated into six groups (A, B, C, D, E and F). The treatments were 0 (control), 1%, 2%, 3%, 4% and 5% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Also, Khanedar et al, (2012) reported that dietary SB 1% significantly improved FCR and decreased FI than those fed 0 or 1.5% dietary SB in male Ross 308 strain broiler chickens. Also, Besseboua et al, (2018) compared the effect of six diets containing dietary SB as (0, 1, 2, 3, 4 or 5 %) on FI and FCR of Arbor Acre broiler chicks. They found that non supplemented SB significantly increased FI compared with other groups.…”
Section: Productive Performancementioning
confidence: 99%
“…Also, Khanedar et al, (2012) reported that dietary SB 1% significantly improved FCR and decreased FI than those fed 0 or 1.5% dietary SB in male Ross 308 strain broiler chickens. Also, Besseboua et al, (2018) compared the effect of six diets containing dietary SB as (0, 1, 2, 3, 4 or 5 %) on FI and FCR of Arbor Acre broiler chicks. They found that non supplemented SB significantly increased FI compared with other groups.…”
Section: Productive Performancementioning
confidence: 99%